Quality of life and self-reported disability in patients with osteoarthritis: Cross-sectional descriptive study - Tarun Kumar; Vandna Pandey; Ashok Kumar; Abhay Elhence; Vikas Choudhary (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Osteoarthritis (OA) is a chronic disease in which the cartilage in the joints deteriorates and the bones rub against each other, causing pain, stiffness, and restricted range of motion. This is an age-related condition that affects initially isolated joints or joints on one aspect of the body. The aim of the study is to identify quality of life and self-reported disability in patients with osteoarthritis. MATERIALS AND METHODS: A cross-sectional descriptive study was conducted in Orthopedic O.P.D. of tertiary care hospital. Study was conducted on 150 samples with convenience sampling at orthopedic O.P.D. Data were collected with standardized tools SF-36 with domains physical functioning (PF), role physical (RP), vitality (VT), mental health (MH), role emotional (RE), social functioning (SF), bodily pain (BP) general health (GH), and Western Ontario and McMaster Universities Arthritis Index (WOMAC) questionnaires with domains pain, stiffness, and functional disability. Descriptive statistics and inferential statistics were used for data analysis such as mean, frequency, percentage, standard deviation, and Chi-square test. RESULTS: Out of 150 samples, 103 were females, 114 were Hindu, and 131 were married. Highest mean score in RE domain of SF-36 was 60 with SD 38.43 indicating that patients had low impact on quality of life, whereas lowest mean score was 35.33 with SD 32.67 indicating that patients had severe impact in RP domain. In WOMAC index, patients had highest pain in climbing stairs, stiffness during morning, and functional difficulty during doing heavy domestic work, whereas lowest pain in resting, stiffness in evening, and functional difficulty during lying in bed. CONCLUSION: Patients with OA had poorer quality of life in domains PF, RP, VT, BP, and GH. Patients with osteoarthritis showed highest self-reported disability in terms of pain in climbing stairs, stiffness during morning, and functional difficulties in doing heavy domestic duties.